Strategies for the preparation of non-amplified and amplified genomic dengue gene samples for electrochemical DNA biosensing applications - Abdul Rashid, Jahwarhar Izuan; Yusof, Nor Azah; Abdullah, Jaafar; Shomiad @ Shueb, Rafidah Hanim (Royal Society of Chemistry, 2022)
The application of electrochemical DNA biosensors in real genomic sample detection is challenging due to the existence of complex structures and low genomic concentrations, resulting in inconsistent and low current signals. This work highlights strategies for the treatment of non-amplified and amplified genomic dengue virus gene samples based on real samples before they can be used directly in our DNA electrochemical sensing system, using methylene blue (MB) as a redox indicator. The main steps in this study for preparing non-amplified cDNA were cDNA conversion, heat denaturation, and sonication. To prepare amplified cDNA dengue virus genomic samples using an RT-PCR approach, we optimized a few parameters, such as the annealing temperature, sonication time, and reverse to forward (R/F) primer concentration ratio. We discovered that the generated methylene blue (MB) signals during the electrochemical sensing of non-amplified and amplified samples differ due to the different MB binding affinities based on the sequence length and base composition. The findings show that our developed electrochemical DNA biosensor successfully discriminates MB current signals in the presence and absence of the target genomic dengue virus, indicating that both samples were successfully treated. This work also provides interesting information about the critical factors in the preparation of genomic gene samples for developing miniaturized PCR-based electrochemical sensing applications in the future. We also discuss the limitations and provide suggestions related to using redox-indicator-based electrochemical biosensors to detect real genomic nucleic acid genes.